Geology of part of the central Damara belt around the Tumas River, South West Africa - Bunting, F J L (Rhodes University, Faculty of Science, Department of Geology, 1978)
The investigation covering 1500 square kilometres within the central granite zone of the Damara belt, South West Africa, revealed Pre - Damara (Abbabis) basement unconformably overlain by metasediments of the Damara Supergroup. The term Leeukop member is proposed for basal metaconglomerates of the Nosib Group that immediately overlie the basement augen-gneisses. Augen-gneiss clasts are present within the Leeukop metaconglomerates. The Damara orogeny has only partly affected the Abbabis rocks of the Tumas River Inlier but further to the west the Husab suite of red granites and granite-gneisses, as field and geochemical evidence suggest, were derived syntectonically during the Damara orogeny by reactivation of the pre- Damara basement. RÃµssing alaskitic granites represent late stage melts, that were also derived from Pre- Damara basement rocks during orogenesis, which accumulated post-tectonically in structural traps at the base of the Khomas Subgroup. Salem granitoids are present in synclinal structures associated with metasediments of the Khomas Subgroup and syntectonic derivation by anatexis during the Damara orogeny is suggested. In the east the differentiated Gawib granitoid stock was emplaced post- tectonically through basement rocks into the Damara metasediments. A deep seated origin is indicated by high crystallisation temperatures (>8500Â°) obtained from quarternary Qz-An-Ab-Or- Hâ‚‚0 plots. The metamorphic grade increases westwards from medium grade to high grade. In the east, the metapelites contain andalusite, and coexisting muscovite and quartz. This indicates that temperatures of 6000Â° at 3,5- 4 kb pressure were attained. In the west, coexisting wollastonite and anorthite in the Khan gneisses indicate pressure- temperature conditions of 720Â° at 4,5-5 kb. Two tectonic events were responsible for the regional structure. An early Fâ‚ episode produced east- west oriented overturned folds and was followed by an intense Fâ‚‚ episode of isoclinal folding which is responsible for the dominant northeast - southwest regional fabric. The interference of these folds in the proximity of the underlying basement produced the complex dome and basin structures seen in the central and western parts of the area. An Fâ‚ƒ episode of minor importance was also recognized. The presence of continental basement rocks in this central part of the Damara belt is evidence for formation of the orogen by in-situ deformation rather than continental collision.
Keywords: Geology -- Namibia -- Damaraland; Geology, Stratigraphic -- Namibia; Geology -- Namibia -- Tumas River Watershed; Geology -- Namibia